After Fukushima : The Equivalence of Catastrophes - Nancy, Jean-Luc (Book collections on Project MUSE., 2015)
"In this book, the philosopher Jean-Luc Nancy examines the nature of catastrophes in the era of globalization and technology. Can a catastrophe be an isolated occurrence? Is there such a thing as a "natural" catastrophe when all of our technologies nuclear energy, power supply, water supply are necessarily implicated, drawing together the biological, social, economic, and political, Nancy examines these questions and more. Exclusive to this English edition are two interviews with Nancy conducted by Danielle Cohen-Levinas and Yuji Nishiyama and Yotetsu Tonaki"--